A gis-based assessment combined with local ecological knowledge to support the management of juncus acutus l spreading in the floodplain of a protected coastal lagoon - López-Juambeltz F, L Rodríguez-Gallego, JM Dabezíes, C Chreties, S Narbondo; D Conde (2020) (My University, 2020)
The floodplains of brackish coastal lagoons are subject to a highly dynamic hydrological regimen mainly due to their intermittent connection with the ocean. Coastal lagoons generally support fisheries, while livestock ranching and human settlements are found in the floodplain. Therefore, it is common practice to artificially open the sand barrier to avoid floods and manage fish stocks. Saltmarsh species are subject to grazing pressure and to changes in flooding and salinity regimens, affecting plants&rsquo community structure. In the Laguna de Rocha Protected Landscape, a shallow brackish coastal lagoon located in Uruguay (South America), livestock ranchers complain about the spreading of the native cyperacea Juncus acutus L. The plant forms dense mats in the outermost zones of the floodplain, apparently displacing natural grasslands where the cattle graze. Also, stakeholders have encouraged the park authorities to artificially open the lagoon to obtain short-term benefits for fisheries and cattle raising. The study evaluated the increase in the surface area occupied by J. acutus and analyzed the possible causes of this increase as a basis for suggesting management actions. Historical and current aerial and satellite images, historical hydrological and climatic data and local ecological knowledge about the biology of the species and its spatial distribution over time were analyzed. The results indicate that J. acutus expanded in the floodplain of Laguna de Rocha, possibly starting ca. 2000, to cover less than 100 ha of the study area at low and high density. The results confirm most of the information obtained from the local stakeholders, whose local ecological knowledge was highly useful in understanding some local processes and providing information regarding periods for which data were not available. The expansion of J. acutus can be explained by a multiplicity of causes that acted synergistically to favor the species through a series of changes in the management of the sand barrier, livestock management and climate variability. However, a quantification of the economic effects of J. acutus on cattle feeding and fisheries is needed. Possible actions to control J. acutus expansion involve management of the grazing pressure using sheep, burning with fire, mechanical removal and avoiding artificial opening of the lagoon to allow larger and longer floods to occur and permit recovery of the previous, more natural hydrological regime. Our results suggest that it is important to be cautious before taking management actions to avoid costly solutions that are only short-term palliatives that could trigger other unforeseen environmental impacts.
Keywords: Artificial opening of sand barriers; Protected areas; Laguna de Rocha